The Effect of the Ring Mains Units for On-Line Partial Discharge Location With Time Reversal in Medium Voltage Networks - Antonella Ragusa; Peter A. A. F. Wouters; Hugh G. Sasse; Alistair Duffy (IEEE Access, 2022)
The performance of a new on-line partial discharge (PD) location method based on the Electromagnetic Time Reversal (EMTR) theory and the Transmission Line Matrix (TLM) method are investigated for characterization of Medium-Voltage (MV) networks. The distortion of the PD signal during its propagation along a cable connection including network components modelled based on experimental data is reproduced in simulation and the effectiveness of the EMTR-based method to localize the PD source is analyzed. In particular, the effects of the ring main units (RMUs), that behave as a complex impedance, the variation with frequency of the MV cable impedance and the reflection patterns, due to impedance mismatches, are considered and investigated. Simulation results are given showing the performance of the EMTR method in two different networks configurations: the former one with a RMU at the end of a MV cable and the latter one with a second MV cable connected to the RMU of the first configuration having a distribution transformer at its far end. The results show that the EMTR method is able, with only a single observation point, to localize PDs also in the presence of RMU with a relative error, with respect to the line length, of approximately 1%.